Stent Configurations And Its Effectiveness In Renal Artery Aneurysm - Bakar, Muhammad Haziq Abu (2019)
Renal artery aneurysm (RAA) is a disease in which the renal artery is dilated at a particular point. Endovascular, a treatment for aneurysm by inserting a stent (or flow diverter (FD)) in the aneurysm effected artery is the preferable choice today. In the hemodynamic study, the focus on RAA study is still lacking compared to other aneurysm conditions. In this thesis, FSI simulations and PIV experimental work of RAA condition for different configurations of FD were conducted to study its effectiveness in treating RAA. Flow patterns, wall shear stress (WSS), deformation and von Mises stress parameters were analysed. The FD configurations were divided into two: (1) different porosity (65% to 80%); (2) different thickness (0.05 mm to 0.09 mm). In addition, Quemada rheological model was used to represent blood material properties. This material model considers all the important factor that affect the viscosity of the blood including shear rate, plasma viscosity and red blood cells. Comparison between simulations and PIV experimental data showed good agreement with average percentage difference around 5%. The blood circulation inside the aneurysm reduced drastically when FD placed in the RAA model. A reduction around 90% for WSS and 40% for deformation when FD was not presence. Additionally, von Mises stresses experienced by RAA was larger stress when no FD placed inside the RAA. Secondly was comparison of FD with different thicknesses. For the flow pattern, FD with thickness of 0.05 mm had blood circulation inside the aneurysm dome. additionally, the WSS recorded for it was the largest among all three cases. Furthermore, as the FD thickness increased, the maximum von Mises stress experienced decreases. In conclusion, FD with porosity percentage of 65% is sufficient to produce the desired and comparable results as with FD with greater percentage porosity. In terms of the FD thickness, the suggested minimum FD thickness to prevent from having blood circulation inside the aneurysm sac is 0.07 mm.